Deep traps in KMgF₃ and LiBaF₃ crystals - Gektin, A.V.; Shiran, N.V.; Neicheva, S.V.; Krasovitskaya, I.M. (Functional Materials, 2004)
The influence of the high temperature annealing in air to the deep traps formation in KMgF₃ and LiBaF₃ fluoroperovskites was the subject of this study. An additional absorption and blue emission connected with O²⁻ ions presence in annealed crystal were revealed. The thermal destruction of colour centres in x-irradiated samples is accompanied by intensive recombination luminescence in high temperature TSL peaks. This phenomena was explained by pyrohydrolysis of crystal surface and oxygen diffusion into the crystal volume. Hydrolysed crystals were found to store the energy under UV irradiation.